Spatial Language of Young Children During Block Play in Kindergartens in Urban China - Yang, Xiaoli; Pan, Yuejuan (Frontiers in Psychology, 2021)
Spatial language is an important predictor of spatial skills and might be inspired by peer interaction and goal-oriented building behaviors during block play. The present study investigated the frequency, type and level of children’s spatial language during block play and their associations with the level of block play by observing 228 young children in classrooms equipped with unit blocks and allowing free play on a daily basis. The findings showed that during block play, young children used more words about spatial locations, deictic terms, dimensions and shapes and fewer words about spatial features or properties and spatial orientations or transformations. Spatial locations were used most frequently, and young children tended to use vertical location words to represent the corresponding location. Most young children used gesture in conjunction with spatial deictic terms. Among shape words, tetragon words were frequently used, and the representation of spatial shapes showed alternatives, collective tendencies and gender differences. The use of spatial language during the play process had a significant positive correlation with the age, the construction structure and form of block building.